Enhanced specific energy of silver-doped MnO2/graphene oxide electrodes as facile fabrication symmetric supercapacitor device. (June 2021) - Mane, V.J.; Kale, S.B.; Ubale, S.B.; Lokhande, V.C.; Lokhande, C.D.
Abstract: The present work is about the preparation of silver (Ag)-doped manganese oxide (MnO2 )/graphene oxide (GO) composite thin films are deposited by a facile and binder-free successive ionic layer adsorption and reaction (SILAR) method for the first time. The Brunauer-Emmett-Teller (BET) study revealed the nanosheets of MnO2 –Ag3/GO exhibit high specific surface area of 192 m 2  g −1 . The tailored flower-like morphology and interconnected nanosheets of MnO2 –Ag3/GO electrodes achieved high electrochemical performance. The maximum specific capacitance (Cs) of 877 F g −1 at the scan rate of 5 mV s −1 is obtained for MnO2 –Ag3/GO electrode tested in 1 M sodium sulfate (Na2 SO4 ) electrolyte with capacity retention of 94.57% after 5000 cycling stability. The MnO2 –Ag3/GO composite-based flexible solid state symmetric supercapacitor (FSS-SSC) device delivered Cs as 164 F g −1 with specific energy of 57 Wh kg −1 at specific power of 1.6 kW kg −1 and capacitive retention of 94% after 10, 000 cycles. Graphical abstract: Figure showing the specific energy versus specific power and flexible solid state symmetric supercapacitor device of configuration MnO2 –Ag3/GO//PVA-Na2 SO4 //MnO2 –Ag3/GO electrodes. Image 1 Highlights: The MnO2, Ag-doped MnO2 and MnO2 -Ag3/GO thin films are synthesized using SILAR method. TThe MnO2 -Ag3/GO composite electrode showed electrochemical specific capacitance of 877 F g −1 at scan rate of 5 mV s −1 . The symmetric supercapacitor device showed specific energy of 57 Wh kg −1 with specific power 1.6 kW kg −1 . The symmetric device glows 211 red LEDs for more than 180 s after 30 s charging with output power of 620 mW cm −2 .